L- pre-open and L-semi-p-open Sets - Gasim, S. G. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The purpose of this paper is to study new types of open sets in bitopological spaces. We shall introduce the concepts of L- pre-open and L-semi-p-open sets